STUDI DESKRIPTIF TINGKAT KEPUASAN KONSUMEN FOOD COURT CITY OF TOMORROW SURABAYA DARI PERSPEKTIF PERUBAHAN LIFESTYLE MASYARAKAT MODERN - Heny Widyaningsih (Tourism Retailing+, 2013)
This study was conducted to determine the extent of interest and the level of consumer satisfaction with quality products and quality service food court City of Tomorrow Surabaya related to the lifestyle of modern society and to test whether the quality of product and service quality affects consumer satisfaction.The data analysis technique used in this study is Customer Satisfaction Index, Importance and Performance Matrix, cross tabs and Linear Regression and Cluster analysis based Activity, Interest and Opinion respondents to identify lifestyle. The result showed that most consumers are in cluster 2 is adopt a lifestyle of modern society. Consumers are satisfied with the quality of product and service quality as well as a food court City of Tomorrow product quality and service quality significantly affect either simultaneously or partially to the consumer's satisfaction with the quality of service that has the most dominant effect on satisfaction.